Percutaneous Endoscopic Transforaminal Discectomy versus Conventional Open Lumbar Discectomy for Upper Lumbar Disc Herniation: A Comparative Cohort Study. (3rd March 2020) - Li, Ziquan; Zhang, Cong; Chen, Weisheng; Li, Shugang; Yu, Bin; Zhao, Hong; Shen, Jianxiong; Zhang, Jianguo; Wang, Yipeng; Yu, Keyi
Abstract : Background . Percutaneous endoscopic transforaminal discectomy (PETD) is regarded as a viable alternative option for upper lumbar disc herniation (LDH). However, few studies have evaluated PETD for upper LDH, and no study has compared the advantages of endoscopic procedures versus conventional surgery. The present study was aimed at comparing the surgical outcome and safety of PETD versus conventional open lumbar discectomy in the treatment of upper LDH. Methods . Data from 42 patients treated for upper LDH from July 2015 to July 2018 were retrospectively analyzed, including 21 patients treated with PETD (PETD group) and 21 patients treated with conventional posterior lumbar discectomy (open group). The two groups were compared regarding demographic information, physical examination, radiological evaluations, and perioperative indicators. The clinical outcomes were assessed in accordance with the Oswestry Disability Index (ODI), visual analog scale (VAS), and modified MacNab criteria. Results . The postoperative ODI and VAS scores were significantly improved in both groups compared with the preoperative baseline values (P < 0.001 ), and the satisfactory rate was 90.5% in both groups in accordance with the modified MacNab criteria. There were no significant differences between the two groups in the clinical outcomes and complication rate (P > 0.05 ); however, compared with the open group, the PETD group had significantly less blood loss, less postoperative drainage, shorter operation time, and shorter postoperative hospitalization (P < 0.001 ). Conclusions . PETD has a similar outcome to the conventional surgical method for the treatment of upper LDH but provides the typical advantages of minimally invasive procedures such as reduced iatrogenic injury, minimal activity restrictions, and accelerated ambulation recovery postoperatively.